Comprehensive geriatric assessment-based screening and integrated intervention for osteosarcopenia risk factors in older adults: an application analysis in patients aged ≥80 years - Tian ZHANG; Jiangming SHA; Liming JIANG; Quanzhong YIN; Yihang GU (Zhongguo Linchuang Yixue)
Objective To explore the utility of comprehensive geriatric assessment (CGA) in screening risk factors for osteosarcopenia (OS) among older adults (≥80 years old) and to evaluate the therapeutic efficacy of CGA-guided integrated interventions for OS. MethodsA total of 420 patients aged ≥80 years, recruited from the Department of Geriatrics, General Practice of The Affiliated Jiangyin Hospital of Nantong University, and community health centers from January 2022 to October 2024, were enrolled. Participants were classified into OS (n＝139) and non-OS (n＝281) groups based on diagnostic criteria. CGA was utilized to compare differences in general characteristics, laboratory indicators, comorbidities between groups. Binary logistic regression analysis identified independent risk and protective factors. Subsequently, 40 OS patients were randomly assigned to an intervention group (n＝20) receiving integrated interventions including nutritional support, exercise training, and psychological management or a control group (n＝20, receiving routine care). Appendicular skeletal muscle mass index (ASMI), grip strength, gait speed, and bone mineral density (BMD) T-score were compared between groups after 3 months. ResultsThe prevalence of OS in this cohort was 33.1%. Compared to the non-OS group, the OS group exhibited significant differences in age, body mass index (BMI), smoking history, comorbidity index, concomitant medication, cognitive impairment, visual and hearing impairment, sleep disorders, depression, marital status, social participation, activities of daily living, nutritional risk, total cholesterol, uric acid, and constipation (P＜0.05). Logistic regression analysis identified age and comorbidity index as significant risk factors for OS, while BMI, married status, total cholesterol, and activities of daily living (assisted and independent) served as protective factors. The intervention group demonstrated significant improvements in grip strength, gait speed, BMD T-score, and male ASMI compared to controls (P＜0.05). ConclusionsCGA demonstrates clinical utility in systematically identifying risk factors for OS in the old population. Multimodal interventions guided by CGA effectively improve musculoskeletal function in elderly OS patients.